Determination Of Physical Activity Level In The Caregiving Of Schizophrenia Patients - Sefa Lok; Neslihan Lok (Türk Spor ve Egzersiz Dergisi)
The aim of this study was to evaluate the physical activity levels of the caregivers of the schizophrenic patients.This research was descriptive and was conducted with face-to-face interviews with relatives of schizophrenia patients enrolled in a Community Mental Health Center. The sample of the study consisted of 124 individuals who agreed to participate in the study. Socio-demographic data form and International Physical Activity Questionnaire were used for data collection. In order to evaluate the demographic data of the study, t-test and Kruskal-Wallis test were used in order to evaluate the relationship between number and percentage distributions, socio-demographic characteristics and International Physical Activity questionnaire. The mean age of the participants was 38,26 ± 4,26, 61,32% female, 38,68% male, 34,65% married, 81,65% single, 10,47%. 27.49% are primary school / middle school, 33% are high school and 29.04% are university graduates. When the body mass index of the participants was evaluated, 65.35% were overweight, 54.95% were inactive and 33.85% were given care for 6-10 years. When sociodemographic and physical activity levels are compared; 41,17% of women, 19,18% of those with care years 1-5 years and 52,46% of overweights were found to be inactive in terms of physical activity and the difference was statistically significant (p lt;0,05).  In our study, it was observed that the sociodemographic characteristics of the participants significantly affected the physical activity level.